Optimization of the automotive service centre network for new entrans into Czech and Slovak markets - Pekárek, Jan; Schüller, David (Univerzita Pardubice, 2018)
The automotive sector is the main driver of industry in both the Slovak and Czech economies. In recent years, rapid and substantive changes have been seen in the development of automotive distribution channels in the Slovak and Czech Republics and this trend can be expected in the future as well. The purpose of this paper is to present a new approach to determine the optimal location of service centres for customers of the automotive industry. The method proposed maximizes a weighted customer utility in terms of density of car-owning residents and the travel distance they need to overcome to reach the nearest station. The application of the proposed method allows automotive companies which are planning to enter new markets to create an optimal distribution network of service centres for customers in the Slovak and Czech Republics. The optimization model approximates the correct number of service centres according to evidence from other countries in the European Union and calculates their optimal spatial placing based on various criteria.
Keywords: optimization; new entrants into markets; distribution network; automotive industry; service centres location; C61; L10; L19